2011
DOI: 10.1007/s00374-011-0644-3
|View full text |Cite
|
Sign up to set email alerts
|

Soil biochemical activities and the geometric mean of enzyme activities after application of sewage sludge and sewage sludge biochar to soil

Abstract: There is a need to improve the way in which wastes, such as sewage sludges, are managed and a potential way to proceed would be to transform them into biochar. On the other hand, there is a growing interest in the use of soil biochemical properties as indicators of soil quality because they are sensitive to alterations in soil management. Thus, we have studied the effect of a biochar obtained from sewage sludge on soil biochemical properties in an organic soil using two doses of biochar and comparing these res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
166
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 342 publications
(188 citation statements)
references
References 45 publications
15
166
2
5
Order By: Relevance
“…The initial organic matter mineralization was very similar in all cases (C parameter ranged from 6.07 to 7.91) according to Mén-dez et al (2012), who found an increment of CO 2 emissions after application at the same rate after application of biochar prepared from sludge to a similar sandy soil or results obtained by Smith (2010). Nevertheless, Paz-Ferreiro et al (2012) found a negative priming effect after sewage sludge biochar application (prepared at 650 • C) to an Umbrisol. Indeed, Zimmerman et al (2011) concluded that discrepancies in C mineralization of biochar-treated soils are likely due to the type of both soil and biochar, the duration of the experiment and the dose of used biochar.…”
Section: Substratementioning
confidence: 53%
“…The initial organic matter mineralization was very similar in all cases (C parameter ranged from 6.07 to 7.91) according to Mén-dez et al (2012), who found an increment of CO 2 emissions after application at the same rate after application of biochar prepared from sludge to a similar sandy soil or results obtained by Smith (2010). Nevertheless, Paz-Ferreiro et al (2012) found a negative priming effect after sewage sludge biochar application (prepared at 650 • C) to an Umbrisol. Indeed, Zimmerman et al (2011) concluded that discrepancies in C mineralization of biochar-treated soils are likely due to the type of both soil and biochar, the duration of the experiment and the dose of used biochar.…”
Section: Substratementioning
confidence: 53%
“…Production of biochar from latrine waste and sewage sludge could have potential uses in heavy metal removal from wastewater. Pyrolysis of these fecal wastes to biochar could recover carbon and nutrients (Hossain et al, 2011;Paz-Ferreiro et al, 2012;Mendez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Increased sorption capacity of the soil was reported by Paz-Ferreiro et al, (2012) after amendment with biochar and mineral components into the soil (Paz-Ferreiro et al, 2012). Ameloot et al, (2013b) showed that the type of biochar alone has a significant effect on soil enzymatic activity, they proved that poultry litter biochar produced at 400°C and amended to soil caused a significant increase in the activity of dehydrogenases enzyme, whereas the same biochar obtained at 500°C reduced the activity of these enzymes over two times compared to the control (Ameloot, 2013b.).…”
Section: Uses Of Poultry Litter Biochar As a Soil Amendmentmentioning
confidence: 94%